Federal Antibias Legislation and Academic Freedom: Some Problems with Enforcement Procedures - HUNTER, Howard (Institutional Knowledge at Singapore Management University, 1978)
Since World War II, changes and developments in various policies of the American government have given rise to a vast array of complex regulations applicable to institutions of higher learning that receive federal financial support.' Before World War II the federal government was not wholly divorced from matters of higher education, but financial support came principally from state or local governments and from private sources. The shift to a more active federal role has profoundly affected the nation's private colleges and universities.' While state schools have always had a close relationship with their supporting governments, the increased federal role has seriously endangered the institutional autonomy of private universities. As one scholar has noted, "The American university has traverse[d], in recent decades, a considerable part of the road froman autonomous financially independent model to an essentially publicly supported, interdependent institution."